Death and taxes: taxation issues and consequences that arise on the final frontier - Wilson-Rogers, Nicole; Morgan, Annette; Pinto, Dale (Taxation Institute of Australia, 2012)
Complex taxation issues can arise on and following the death of a taxpayer, in relation to diverse areas of revenue law, and because of inconsistency between the treatment at general law and taxation law of some of the key relationships that arise on the death of a taxpayer. Another factor is the proposed reform of Div 128 of the Income Tax Assessment Act 1997 (Cth). This article discusses some of the income tax, CGT and superannuation issues, by reference to a case study. The article considers the issues that arise in relation to three distinct phases after a taxpayer’s death, namely, the period between death and administration of the deceased estate, the period during which the executor distributes assets to the beneficiaries, and the period following the asset being distributed to the beneficiary, including an analysis of the issues that arise on the establishment and maintenance of a testamentary trust